Performing the Gospels in Byzantium : sight, sound, and space in the divine liturgy - Betancourt, Roland (Cambridge : Cambridge University Press, 2021)
Tracing the Gospel text from script to illustration to recitation, this study looks at how illuminated manuscripts operated within ritual and architecture. Focusing on a group of richly illuminated lectionaries from the late eleventh century, the book articulates how the process of textual recitation produced marginalia and miniatures that reflected and subverted the manner in which the Gospel was read and simultaneously imagined by readers and listeners alike. This unique approach to manuscript illumination points to images that slowly unfolded in the mind of its listeners as they imagined the text being recited, as meaning carefully changed and built as the text proceeded. By examining this process within specific acoustic architectural spaces and the sonic conditions of medieval chant, the volume brings together the concerns of sound studies, liturgical studies, and art history to demonstrate how images, texts, and recitations played with the environment of the Middle Byzantine church.
Beginnings and Initials: Text, Image, and Sound -- Miniatures and Marginalia: A Visual Grammar and Syntax -- Faltering Images: Iconography between Reading, Error, and Confusion -- The Reading of the Lectionary: Recitation, Inspiration, and Embodiment -- The Sound of the Lectionary: Chant, Architecture, and Salvation -- Polyvalent Images: Iconography between Image, Space, and Sound.
Title from publisher's bibliographic system (viewed on 22 Feb 2021).
Keywords: Illumination of books and manuscripts, Byzantine; Senses and sensation -- Religious aspects -- Orthodox Eastern Church; Liturgy and art; Lectionaries